Application Of Information Compression to Create New Hash Functional Algorithms of Rectangal Matrix Introduction - Akhmadaliev Shakhobidin Sharifovich; Hasanov Xayrullo Maxmudovich; Botirov Muzaffar Mansurovich (Zien Journals, 2022)
In article on the basis of results of research of properties of compression and single-sided rectangular matrixes the new algorithm of hashing function is developed
Keywords: rectangular matrix; data blocks; compression